Analysis of the Influence of Migration of Indonesian Workers (TKI) Abroad on Indonesia's Economic Growth - Pebri Kurniawan; Ukhti Ciptawaty; I Wayan Suparta; Arivina Ratih YT; Heru Wahyudi (Lafadz Jaya Publisher, 2024)
This research aims to analyze the influence of migration of Indonesian Migrant Workers (TKI) abroad on Indonesia's economic growth. This type of research is quantitative research. This research uses secondary data sourced from World Bank and BP2MI data. The data used in this research is time series data from 1983-2019. The method used in this research is the Autoregressive Distributed Lag (ARDL) model data analysis method. The research results show that in the short-term migrant workers abroad have a positive and significant effect on Indonesia's economic growth, while remittances in the short term have a negative and significant effect on Indonesia's economic growth. Meanwhile, in the long term, migrant workers abroad and remittances have an insignificant negative effect on economic growth in Indonesia.